Who governs Southern Europe? : regime change and ministerial recruitment, 1850-2000 - Almeida, Pedro Tavares de.; Pinto, António Costa; Bermeo, Nancy Gina, 1951- (London ; Portland, OR : F. Cass, 2003)
This collection is a comprehensive, empirical account of the composition and patterns of recruitment of ministerial elites in Southern Europe throughout the last 150 years, thus encompassing different historical circumstances and political settings.
Book Cover; Title; Contents; Preface; Portuguese Ministers, 1851 1999: Social Background and Paths to Power; Ministers and Regimes in Spain: From the First to the Second Restoration, 1874 2002; Ministers in Italy: Notables, Party Men, Technocrats and Media Men; Ministerial Elites in Greece, 1843 2001: A Synthesis of Old Sources and New Data; Ministerial Elites in Southern Europe: Continuities, Changes and Comparisons; Abstracts; Notes on Contributors; Index.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Europe, Southern -- Politics and government; Elite (Social sciences); Power (Social sciences); Spain -- Politics and government; Portugal -- Politics and government; Italy -- Politics and government; Greece -- Politics and government; Élite (Sciences sociales); Pouvoir (Sciences sociales); Espagne -- Politique et gouvernement; Portugal -- Politique et gouvernement; Italie -- Politique et gouvernement; Grèce -- Politique et gouvernement; HISTORY -- Historical Geography; Elite (Social sciences); Politics and government; Power (Social sciences); Southern Europe; Greece; Italy; Portugal; Spain